2013
DOI: 10.1186/1757-2215-6-62
|View full text |Cite
|
Sign up to set email alerts
|

Metformin decreases the incidence of ovarian hyperstimulation syndrome: an experimental study

Abstract: BackgroundIn assisted reproduction cycles, gonadotropins are administered to obtain a greater number of oocytes. A majority of patients do not have an adverse response; however, approximately 3-6% develop ovarian hyperstimulation syndrome (OHSS). Metformin reduces the risk of OHSS but little is known about the possible effects and mechanisms of action involved.ObjectiveTo evaluate whether metformin attenuates some of the ovarian adverse effects caused by OHSS and to study the mechanisms involved.Material and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…In human breast cancer, VEGF stimulation increased the degree of ERK1/2 phosphorylation, indicating the activation of ERK1/2-associated intra cellular pathways (25). A previous study reported that metformin decreased vascular permeability and expression of VEGF, suggesting that metformin normalizes vascular permeability by regulating VEGF levels (26). Additionally, the effects of metformin and DDP on VEGF modulation have been also described in ovarian cancer in vivo and in Lewis lung cancer rats (3,27).…”
Section: Discussionmentioning
confidence: 86%
“…In human breast cancer, VEGF stimulation increased the degree of ERK1/2 phosphorylation, indicating the activation of ERK1/2-associated intra cellular pathways (25). A previous study reported that metformin decreased vascular permeability and expression of VEGF, suggesting that metformin normalizes vascular permeability by regulating VEGF levels (26). Additionally, the effects of metformin and DDP on VEGF modulation have been also described in ovarian cancer in vivo and in Lewis lung cancer rats (3,27).…”
Section: Discussionmentioning
confidence: 86%
“…39,40 Combining these previous observations, the "programming" antitumor growth effect of metformin may be based on inhibiting neovascularization in Walker 256 tumor-bearing rats.…”
Section: -25mentioning
confidence: 99%
“…One hallmark of neoangiogenesis is the increased vascular endothelial growth factor (VEGF) levels. In an ovarian tumor treated with metformin, the neoangiogenesis was inhibited showing low levels of VEGF [39,40]. …”
Section: Discussionmentioning
confidence: 99%